Integration of Spiritual Healing and Islamic Education through Ruqyah - Habibi, Mukhlas; Sholihah, Alfiani Rif’atus; Hidayati, Lailatul; Mukaromah, Muhimmatul (Cendekia: Kependidikan dan Kemasyarakatan, 2025)
This study aims to analyze the integration between spiritual healing and Islamic education in the practice of ruqyah in Ponorogo. It has been perceived solely as a method of spiritual healing through reciting verses from the Qur'an and special prayers. Some researchers said that it not only serves as therapy but also as Islamic education. This study employed a qualitative case study approach, focusing on the ruqyah practices of Jam'iyyah Ruqyah Aswaja (JRA) Batoro Katong Ponorogo. The data was obtained through interviews, observations, and documentation. Then, it was analyzed using the Miles and Huberman model. The findings reveal that ruqyah serves a dual function: first, as a means of healing for individuals experiencing medical, non-medical, or psychological disorders; second, as an instrument of Islamic education that instills the values of faith, worship, and morals in patients. The integration of these two functions shows that ruqyah can be positioned as a holistic religious practice, combining therapeutic and pedagogical aspects. This study implies that ruqyah can be developed as an integrative non-formal model of Islamic education, serving not only as a spiritual healing therapy but also as a medium for nurturing faith, worship, and moral values within the community.